Characterising heterogeneity and the role of attitudes in patient preferences: A case study in preferences for outpatient parenteral intravenous antimicrobial therapy (OPAT) services. (March 2021) - Hess, Stephane; Meads, David; Twiddy, Maureen; Mason, Sam; Czoski-Murray, Carolyn; Minton, Jane
Abstract: Choice modelling techniques have established themselves as a key analysis tool in health economics and have been used to understand patient and practitioner preferences across a wide variety of settings. A key interest in recent years has been the incorporation of ever more flexible levels of heterogeneity in preferences across individual decision makers, and in particular a growing interest in the potential role that attitudes and perceptions might play in healthcare choices. At the same time however, many applications simply apply these new tools without then investigating the resulting richness in the results. This paper not only presents a novel application of hybrid choice modelling in health, by looking at preferences for outpatient parenteral intravenous antimicrobial therapy (OPAT), but also carefully explores the findings in terms of sources of heterogeneity, disentangling the role of attitudes from other heterogeneity. We find that a large share of the heterogeneity can be attributed to two key underlying attitudinal constructs, related to the general attitude towards hospitals and whether responsibility for healthcare should lie with the patient or the practitioner. Especially the latter accounts for more than 60% of the overall heterogeneity in preferences for the type of treatment. These results may help design services that are suitable and appealing for a wide variety of patients as well as providing some insights into how nudging of attitudes and perceptions could help drive patients towards safer and more cost-effective treatment options.